2008
DOI: 10.1590/s0103-84782008000700040
|View full text |Cite
|
Sign up to set email alerts
|

Tipos e concentrações de citocinina na multiplicação in vitro de pitangueira

Abstract: O trabalho teve como objetivo avaliar o efeito de diferentes tipos e concentrações de citocinina na multiplicação in vitro de pitangueira. Os tratamentos constituíram-se de diferentes concentrações de citocinina adicionada ao meio de cultura (zero; cinco; dez µM) e três diferentes citocininas (BAP; 2iP; zeatina). O meio utilizado foi WPM suplementado com 100mg L-1 de mio-inositol, 30g L-1 de sacarose e solidificado com ágar na concentração de seisg L-1. Segmentos caulinares com três ou quatro gemas, sem o ápic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 5 publications
1
2
0
2
Order By: Relevance
“…We observed a gradual improvement in the number of shoots formation according to the raise of the BAP concentration, from 1.0 up to 2.5 µM. A similar result was reported by Souza et al (2008) in E. uni ora, reporting from 1.20 to 2.35 shoots per explant in the range of 0.0 to 5.0 µM of BAP, while da Silva et al…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…We observed a gradual improvement in the number of shoots formation according to the raise of the BAP concentration, from 1.0 up to 2.5 µM. A similar result was reported by Souza et al (2008) in E. uni ora, reporting from 1.20 to 2.35 shoots per explant in the range of 0.0 to 5.0 µM of BAP, while da Silva et al…”
Section: Resultssupporting
confidence: 89%
“…There were no statistically signi cant differences for chlorophyll a and b contents, as well as for the content of total chlorophyll and chlorophyll a/b ratio among the immersion systems, while the content of carotenoids revealed statistically signi cant differences, with the highest mean obtained in the PIS/GE (Table 4). (Souza et al 2008) suggested the use of a range of BAP concentration from 2.0 to 4.0 µM for the vegetative multiplication of the species, resulting in higher numbers of shoots and buds for higher BAP concentrations. On the other hand, much higher concentrations of BAP (50 µM) were reported as phytotoxic for the explants.…”
Section: Resultsmentioning
confidence: 99%
“…de brotos variou, em média, entre 2,5 e 2,2 por explante, nas concentrações 1µM e 4µM da citocinina, respectivamente, registrando leves diminuições a partir do aumento na concentração desse fitorregulador (Sukartiningsih & Ide, 1999). Efeito contrário para o número de brotações foi obtido em segmentos caulinares de Eugenia uniflora L. (pitangueira) cultivados por 45 dias em meio WPM, demostrando uma relação diretamente proporcional ao aumento das concentrações, 0 a 10µM, das citocininas BAP, 2iP e ZEA (Souza et al, 2008).…”
Section: Resultsunclassified
“…Essa espécie normalmente é propagada por estacas, no entanto, ainda não há um protocolo de propagação por estaquia definido (OLIVEIRA et al, 2009;OLIVEIRA et al, 2001b Ciência Rural, v.41, n.9, set, 2011. para realizar a micropropagação de uma planta frutífera é o domínio da tecnologia de propagação em laboratório, o qual é o resultado de estudos realizados com os fatores que afetam o crescimento e o desenvolvimento das plantas in vitro (SCHUCH & ERIG, 2005;SOUZA et al, 2008).…”
Section: O Tipo De Tampa Utilizado No Frasco De Cultura é Um Fator Quunclassified